Photo-induced cytotoxicity and anti-metastatic activity of ruthenium(ii)–polypyridyl complexes functionalized with tyrosine or tryptophan. Issue 20 (5th May 2017) - Ramu, Vadde; Aute, Sunil; Taye, Nandaraj; Guha, Rweetuparna; Walker, Michael G.; Mogare, Devaraj; Parulekar, Apoorva; Thomas, Jim A.; Chattopadhyay, Samit; Das, Amitava
Abstract : The synergestic effect of oxygen, light, and photosensitizer has found application in photodyanmic therapy (PDT). Abstract : The synergistic effect of oxygen, light, and photosensitizer (PS) has found applications in medicine for the treatment of cancer through photodynamic therapy (PDT). Induction of apoptosis to cancerous cells will prevent tumor metastasis that spreads cancer cells to the neighboring organs/tissues. Herein, we report the two apoptotic Ru(ii )–polypyridyl complexes that are functionalized with pendant amino acid moieties tyrosine (1 ) and tryptophan (2 ), respectively. These two water soluble complexes were found to interact strongly ( K 1a = (1.18 ± 0.28) × 10 5 M −1 and K 2a = (1.57 ± 0.77) × 10 5 M −1 ) with CT-DNA. Isothermal titration calorimetry (ITC) studies revealed that these complexes bind to CT-DNA through an entropically driven process. Both the complexes showed photo-induced cytotoxicity and exhibit apoptotic activity under photo-irradiation conditions. The comet assay indicated that these complexes can damage cellular DNA, which is attributed to the significant build-up of 1 O2 level even on irradiation with low intensity light (10 J cm −2, λ Range 450–480 nm). This photoinduced DNA damage and apoptosis in A549 cells was induced by reactive oxygen species (ROS) and occurred through up-regulation of apoptotic marker caspase-3. Control experiments under dark conditions revealed an insignificant cytotoxicity towards these cells for two photosensitive molecules.